Bacterial colonization in orthopedic surgical tourniquets: A Multicenter study - Baumfeld, Tiago Soares; Frois Temponi, Eduardo; Salzmann Lamego, Luiz Lorentz; Louzada da Costa, Eduardo; Almeida Passos, Glauco; da Silva Marinho, Leandro (Journal of the Foot & Ankle, 2026)
Introduction: Reusable tourniquets are widely used in orthopedic surgeries in Brazil, but national data on their contamination are scarce. The objective of this study is to evaluate the prevalence and microbiological profile of contamination in reusable tourniquets in Brazilian hospitals. Methods: Multicenter observational study conducted in six hospitals. Swabs were collected from 54 tourniquets immediately after surgical use and before disinfection, covering an estimated area of 10 cm2. Samples were cultured and identified by automated methods. The bacterial load was described as the median and interquartile range (IQR), and comparisons between public and private hospitals were performed using Fisher’s exact test and the Mann-Whitney test. Results: The prevalence of contamination was 70.4% (38/54). The median global microbial load was 101 CFU per device (IQR: 0-153), corresponding to approximately 10.1 CFU/cm2. The predominant microorganisms were coagulase-negative Staphylococcus (48.1%) and Staphylococcus aureus (18.5%), with isolation of Pseudomonas aeruginosa, Bacillus sp., and Candida sp. The contamination rate was 78.6% in public hospitals and 61.5% in private hospitals (p = 0.081), with no statistically significant difference in the median bacterial load between institutions (p = 0.412). Conclusion: There is a high prevalence of contamination by clinically relevant pathogens in reusable tourniquets, regardless of the type of hospital. The results indicate systemic failures in reprocessing and suggest the need for high-level disinfection protocols or the adoption of disposable sterile devices to mitigate the risk of cross-contamination.